1996
DOI: 10.1002/(sici)1099-0755(199612)6:4<269::aid-aqc202>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Benthic disturbance by fishing gear in the Irish Sea: a comparison of beam trawling and scallop dredging

Abstract: ABSTRACT1. The distribution of effort for the most frequently used mobile demersal gears in the Irish Sea was examined and their potential to disturb different benthic communities calculated. Fishing effort data, expressed as the number of days fished, was collated for all fleets operating in the Irish Sea in 1994. For each gear, the percentage of the seabed swept by those parts of the gear that penetrate the seabed was calculated.2. For all gears, the majority of fishing effort was concentrated in the norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Many studies examining the effects of scallop harvesting on the marine habitat have been conducted in Europe and Australia, where toothed dredges are used to collect the slightly buried scallops (Chapman et al 1977, Kaiser et al 1996, Jennings & Kaiser 1998, Hill et al 1999, Hall-Spencer & Moore 2000, Veale et al 2000, Jenkins et al 2001, Bradshaw et al 2002. The New Bedford offshore sea scallop dredge rides on 2 shoes and skims over the sea floor, flipping the sea scallops with the sweep chains into the chained bag, and may have less impact on the sea floor than a toothed dredge (Bourne 1964, Caddy 1989.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies examining the effects of scallop harvesting on the marine habitat have been conducted in Europe and Australia, where toothed dredges are used to collect the slightly buried scallops (Chapman et al 1977, Kaiser et al 1996, Jennings & Kaiser 1998, Hill et al 1999, Hall-Spencer & Moore 2000, Veale et al 2000, Jenkins et al 2001, Bradshaw et al 2002. The New Bedford offshore sea scallop dredge rides on 2 shoes and skims over the sea floor, flipping the sea scallops with the sweep chains into the chained bag, and may have less impact on the sea floor than a toothed dredge (Bourne 1964, Caddy 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many studies do not assess disturbances caused by scallop dredging against a background of natural disturbance that occurs over time (Kaiser et al 1996, Jennings & Kaiser 1998, Watling & Norse 1998, Auster & Langton 1999). This is difficult and expensive to do, and as a consequence dredge-impact studies are often hampered by the lack of proper environmental-impact assessment and appropriate monitoring , Jennings & Kaiser 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Jennings & Kaiser 1998, Frid et al 1999, Jennings et al 2002 and most have reported a shift from a highly diverse community with large-bodied animals and a large number of tube-builders in undisturbed areas to communities dominated by smallbodied species, particularly polychaetes, in places that are heavily trawled. A significant depletion of megafauna (large [>10 mm] epifauna or infauna) following trawling has also been demonstrated by a number of authors (De Groot & Lindeboom 1994, Kaiser et al 1996. Megafaunal species are particularly vulnerable because they are typically long-lived and take a relatively long time to reach a reproductive age (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Scallop dredging necessitates the use of heavy dredges that are dragged across the seabed and has been identified as one of the most damaging fishing activities in relation to benthic habitats and species (Kaiser et al 1996, Hall-Spencer & Moore 2000, Jenkins et al 2001. Emergent epifauna, sessile organisms that live attached to the substratum such as sponges, erect bryozoans or anemones, are particularly likely to be impacted by scallop dredging, especially if they are long-lived, slow-growing species with fragile bodies (Guijarro Garcia et al 2006).…”
Section: Introductionmentioning
confidence: 99%